2009
DOI: 10.1080/08958370902942517
|View full text |Cite
|
Sign up to set email alerts
|

Size dependence of the translocation of inhaled iridium and carbon nanoparticle aggregates from the lung of rats to the blood and secondary target organs

Abstract: Currently, translocation of inhaled insoluble nanoparticles (NP) across membranes like the air-blood barrier into secondary target organs (STOs) is debated. Of key interest are the involved biological mechanisms and NP parameters that determine the efficiency of translocation. We performed NP inhalation studies with rats to derive quantitative biodistribution data on the translocation of NP from lungs to blood circulation and STOs. The inhaled NP were chain aggregates (and agglomerates) of either iridium or ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
277
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 348 publications
(289 citation statements)
references
References 16 publications
9
277
0
3
Order By: Relevance
“…Kreyling et al also show that nanoparticles distribute into heart at the first blood circulation and start to aggregate into lung after 4 hours. 39 Our results also supports this idea that drugs are distributed in the blood, which is likely to provide greater access to well perfused organs such as the heart, liver and lung.…”
Section: Resultssupporting
confidence: 77%
“…Kreyling et al also show that nanoparticles distribute into heart at the first blood circulation and start to aggregate into lung after 4 hours. 39 Our results also supports this idea that drugs are distributed in the blood, which is likely to provide greater access to well perfused organs such as the heart, liver and lung.…”
Section: Resultssupporting
confidence: 77%
“…The airways are the primary target organs for inhaled particles but evidence from experimental studies with animals shows that ultrafine particles can translocate to other organs, such as the liver, kidneys, heart and brain 13,[31][32][33] . Although the amount of particles accumulating in secondary target organs, such as the kidney, is many times lower than the lung tissue dose, it may be relevant for carcinogenic processes 34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…Most of the study areas were large cities and the surrounding suburban or rural communities, as specified in the online appendix (pp. [4][5][6][7][8][9][10][11][12][13]. A pooled analysis of all cohort data was not possible due to data-transfer and privacy issues but data from the four Stockholm cohorts (SNAC-K, SALT, 60-y/IMPROVE and SDPP) were pooled, and analysed and denoted as one Similarly, data from the two cohorts from the Netherlands (EPIC-MORGEN and EPIC-PROSPECT) were pooled, analysed and denoted as one [EPIC-NL].…”
Section: Design and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some evidence that the pulmonary hazard of single-walled carbon nanotubes might be increased by the formation of nanotube assemblages in the lungs [60]. Kreyling et al [61] found that the translocation from the rat lung to the circulatory system and other organs of assemblages of Ir (2-4 nm) and C (5-10 nm) nanoparticles was reduced if compared with individual (monodisperse) Ir and C nanoparticles. Albanese and Chan [62] studying the uptake of monodisperse and assemblage of Au nanoparticles by mammalian cells, found the uptake to be dependent on cell type with aggregate uptakes of assemblages ranging from 25% lower to a twofold increase if compared with monodisperse nanoparticles.…”
Section: Determinants Of Human Inhalation Hazards Of Persistent Enginmentioning
confidence: 99%